Concept of Rules “Alyakinu La Yuzalu Bisyaki” Create Independent Person - Kulsum, Umi; Fathan Al Kubro, Muhammad; Khasan, Abdullah (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The rule